Digital protection of power converters employed in doubly-fed induction generator and induction motor using wavelet transform / Ukashatu Abubakar - Ukashatu , Abubakar (2021)
This work comprises two sections, firstly, the execution of an alternative to crowbar for the DFIG-based wind energy conversion system (WECS) is proposed. The deployed crowbar protection scheme is based on a digital algorithm oriented to utilize the d-q axis of the 3-Φ rotor currents. The application of wavelet transforms enables the effective capture, of essential information contained in the high frequency current signals. The crowbar functions to protect the rotor side converter (RSC) from damage, against the high inrush current during short or open circuit fault in the rotor or at the grid. The working of the traditional crowbar is usually characterized with the absorption of reactive power from the grid, which is considered undesirable for the topology presented herein. Furthermore, the presented digital crowbar can discriminate between the actual fault occurrence and momentarily transient. Additionally, the flexibility of wavelet packet transform (WPT) predisposes it to be incorporated within the rotor controller structure and adapted to work as crowbar. The developed d-q WPT-based digital crowbar is capable of generating a faster trip signal with shorter restoration time of ≤7.1